Impact of Household Waste on Public Health: A Literature Review - Nayla Canthyka Yuniaf yuniaf (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2026)
Household waste has become an increasingly prominent environmental and health problem along with population growth, urbanization, and changes in people's consumption patterns. This research uses the literature review method. Household waste is a complex environmental problem, requiring an integrated approach through outreach to increase public awareness of good management. The 3R principle (Reduce, Reuse, Recycle) is applied by reducing the amount of waste, utilizing items that are still useful, and separating waste for recycling. Separation of waste from its source, reducing the use of single-use plastics, as well as support for modern technology and government policies such as Extended Producer Responsibility (EPR) are very important. Waste bank programs and community-based management encourage active community participation in creating sustainable solutions to waste problems.